Digitalization of Bale Beleq in Pejanggik Village Based on a 360-Degree Virtual Reality Tour Website - Sandani, Rezi; Mahendra, I Gede Orka; Widya Dharma, I Gusti Ngurah Adi (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2023)
Cultural heritage preservation plays a vital role in maintaining local identity and historical continuity. Bale Beleq, located in Pejanggik Village, is a significant cultural landmark representing the legacy of the Sasak community in Lombok. However, the lack of digital documentation and limited accessibility hinder public engagement and threaten the sustainability of this cultural heritage. Motivated by the need to preserve and promote local traditions through technology, this research develops a digital platform integrating a website and 360° Virtual Reality (VR) tour. The system aims to provide immersive access to cultural information, enabling users to virtually explore Bale Beleq through panoramic visualization, interactive hotspots, and multimedia narration. The system was developed using the Multimedia Development Life Cycle (MDLC) method, encompassing conceptualization, design, material collection, development, testing, and distribution. Functionality testing using the Black Box method confirmed that all features—such as the virtual tour, gallery, historical descriptions, and audio guides—performed effectively according to design specifications. The evaluation showed that over 90% of users rated the system as highly engaging and informative, proving its potential as an effective medium for cultural promotion and education. Future work will focus on expanding multilingual capabilities, optimizing mobile interfaces, and integrating AI-based virtual guides to enhance interactivity and personalized learning experiences.